Dorsal root ganglion morphometric changes under Oxaliplatin treatment: longitudinal assessment by computed tomography - Apostolidis, Leonidas; Kowalscheck, Lars; Weber, Tim; Godel, Tim; Bendszus, Martin; Kauczor, Hans-Ulrich; Jäger, Dirk; Schlemmer, Heinz-Peter; Bäumer, Philipp (Clinical neuroradiology, 2022)
Purpose Magnetic resonance neurography (MRN) can detect dorsal root ganglia (DRG) hypertrophy in patients with oxaliplatin-induced peripheral neuropathy (OXIPN) but is difﬁcult to apply in clinical daily practice. Aims of this study were (i) to assess whether DRG volume is reliably measurable by routine computed tomography (CT) scans, (ii) to measure longitudinal changes in DRG during and after oxaliplatin administration and (iii) to assess correlation between DRG morphometry and individual oxaliplatin dose. - Methods For comparison of MRN and CT measurements, CT scans of 18 patients from a previous MRN study were analyzed. For longitudinal assessment of DRG size under treatment, 96 patients treated with oxaliplatin between January and December 2014 were enrolled retrospectively. DRG volumetry was performed by analyzing routine CT scans, starting with the last scan before oxaliplatin exposure (t0) and up to four consecutive timepoints after initiation of oxaliplatin therapy (t1-t4) with the following median and ranges in months: 3.1 (0.4-4.9), 6.2 (5.3-7.8), 10.4 (8.2-11.9), and 18.4 (12.8-49.8). - Results DRG volume measured in CT showed a moderately strong correlation with MRN (r = 0.51, p < 0.001) and a strong correlation between two consecutive CTs (r = 0.77, p < 0.001). DRG volume increased after oxaliplatin administration with a maximum at timepoint t2. Higher cumulative oxaliplatin exposure was associated with signiﬁcantly higher absolute DRG volumes (p = 0.005). Treatment discontinuation was associated with a nonsigniﬁcant trend towards lower relative DRG volume changes (p = 0.08). - Conclusion CT is a reliable method for continuous DRG morphometry; however, since no standardized assessment of OXIPN was performed in this retrospective study, correlations between DRG size, cumulative oxaliplatin dose and clinical symptoms in future prospective studies are needed to establish DRG size as a potential OXIPN biomarker.
Online veröffentlicht:9 September 2021
Gesehen am 04.09.2023